PENGARUH KEPUTUSAN PEMBELIAN PRODUK SEPATU VANS : Studi Kasus Wilayah Jakarta Selatan - Teguh Prasetyo (2020)
This research aims to determine the effect of brand image, lifestyle, and product quality on purchasing decisions for shoes. Consumers used in this study are Vans shoe users. Samples were taken as many as 75 respondents, using probability sampling method with simple random sampling technique. Data collection is done through google form, and for data analysis using PLS (Partial Least Square) with smartPLS 3.0 software. The results showed (1) Brand Image does not have a significant influence on Purchasing Decisions with a path coefficient of 0.032. (2) Lifestyle has a significant influence on Purchasing Decisions with a path coefficient of 0.491. (3) Product quality has a significant influence on Purchasing Decisions with a coefficient value of 0.360. The highest contribution is to the influence of Lifestyle on Purchasing Decisions with a path coefficient of 0.491.